(untitled) (International Journal of Food and Nutritional Sciences, 2019)
As small nanosized particles released from cells by exocytosis, exosomes have been recognized as significant modulators in intercellular communication. Henceforth, it is important to note that these extracellular vesicles may inhibit or enhance viral infection from infected to uninfected ones, thus playing an important role in HIV progression